Preparation method of Ni-MOF / Fe / Ni-MOF and magnesium-based composite hydrogen storage material
By preparing NI-MOF/FE/NI-MOF layer-like structural catalysts with the ball mill with MGH2 to form a magnesium-based composite hydrogen storage material, solve the problem of slow response speed at low temperatures, achieve efficient hydrogen and release performance and Stability, suitable for commercialization of hydrogen energy.
Patent Information
- Application Number
- CN202411498457.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The traditional magnesium hydride (MgH2) reacts slowly at low temperatures and requires a higher dehydrogenation temperature, which limits its widespread use in practical applications.
By preparing the layer-like structural catalyst of the NI-MOF/FE/NI-MOF, it is mixed with MGH2 through the ball grinding to form a magnesium-based composite hydrogen storage material to improve its hydrogen performance.
Achieve the hydrogen suction rate of MGH2 at low temperature, enhance the hydrogen storage performance, and improve the stability of the catalyst, and it is suitable for large -scale industrialized production.
Smart Images

Figure CN119368238A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen storage alloys, and in particular to a preparation method of Ni-MOF / Fe / Ni-MOF and a magnesium-based composite hydrogen storage material. Background Art
[0002] The consumption of traditional fossil fuels not only leads to a large amount of greenhouse gas emissions, but also produces a large amount of polluting flue gas, causing serious damage to the environment. Faced with this challenge, hydrogen energy, as a clean and abundant energy source, has attracted much attention due to its zero-pollution characteristics. As an energy product that is easy to store, its role in promoting practical applications is self-evident. Therefore, the development of effective hydrogen storage technology is crucial to the commercialization of hydrogen energy. Among the many hydrogen storage methods, the solid hydrogen storage system based on metal hydrides is considered to be one of the most promising solutions due to its high hydrogen storage density and safety.
[0003] Among these metal hydrides, magnesium hydride (MgH2) shows great potential for reversible hydrogen storage due to its high hydrogen storage capacity (7.6wt%) and low cost. However, MgH2 has a slow reaction rate below 300°C and requires a high dehydrogenation temperature, which limits its widespread adoption in practical applications. To overcome these limitations, researchers have tried to improve the hydrogen absorption and dehydrogenation properties of the Mg / MgH2 system by introducing additives. As catalytically active substances, additives can undergo special chemical interactions with MgH2, thereby improving the hydrogen storage performance of the system.
[0004] In the existing technology, some of them use ball milling technology to coat Cu3(VO4)2 powder on the surface of MgH2 powder, and use Cu3(VO4)2, a bimetallic oxide, to perform synergistic catalytic modification on the Mg / MgH2 system. This modification significantly improves the hydrogen absorption and desorption rate of MgH2 and achieves excellent hydrogen storage performance at low temperatures. However, Cu3(VO4)2 has poor stability as a catalyst.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the objects of the present invention is to provide a method for preparing Ni-MOF / Fe / Ni-MOF to alleviate at least one of the above technical problems.
[0007] A second object of the present invention is to provide a Ni-MOF / Fe / Ni-MOF.
[0008] A third object of the present invention is to provide a magnesium-based composite hydrogen storage material.
[0009] A fourth object of the present invention is to provide a method for preparing a magnesium-based composite hydrogen storage material.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The first aspect of the present invention provides a method for preparing Ni-MOF / Fe / Ni-MOF, comprising the following steps:
[0012] A. Mix the nickel salt solution and the organic ligand solution evenly for a first reaction, and then separate, dry and activate to obtain Ni-MOF;
[0013] B. After dissolving the Ni-MOF, adding iron salt and a reducing agent to carry out a second reaction to obtain Ni-MOF / Fe;
[0014] C. After the nickel salt solution and the organic ligand solution are uniformly mixed, the Ni-MOF / Fe is added to carry out a third reaction to obtain the Ni-MOF / Fe / Ni-MOF.
[0015] Furthermore, the concentration of the nickel salt solution is 1 to 20 mg / mL.
[0016] Preferably, the concentration of the organic ligand solution is 1-20 mg / mL.
[0017] Preferably, in step A, the mass ratio of nickel salt to organic ligand is 1:0.1-2.
[0018] Furthermore, the nickel salt in the nickel salt solution includes at least one of nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel phosphate, nickel carbonate and nickel oxalate.
[0019] Preferably, the solvent in the nickel salt solution includes at least one of methanol, ethanol, ethylene glycol, methyl butyl ketone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile and 1,4-dioxane.
[0020] Preferably, the organic ligand comprises a benzoic acid compound.
[0021] Preferably, the benzoic acid compound includes at least one of terephthalic acid, isophthalic acid, phthalic acid, trimesic acid, pyromellitic acid and mellitic acid.
[0022] Preferably, the solvent in the organic ligand solution includes at least one of methanol, ethanol, ethylene glycol, methyl butyl ketone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile and 1,4-dioxane.
[0023] Furthermore, the temperature of the first reaction is 300-600K, and the time is 1-10h.
[0024] Preferably, the drying activation temperature is 300-500K and the time is 8-24h.
[0025] Furthermore, the iron salt includes at least one of ferric nitrate, ferric chloride, ferric sulfate, ferric acetate, ferric phosphate, ferric carbonate and ferric oxalate.
[0026] Preferably, the added amount of the iron salt is 20-80% of the mass of Ni-MOF.
[0027] Preferably, the reducing agent comprises at least one of sodium borohydride, lithium aluminum hydride, lithium borohydride, sodium cyanoborohydride, lithium triethylborohydride, dimethyl borane and THF borane.
[0028] Preferably, the amount of the reducing agent added is 10 to 90% of the mass of Ni-MOF.
[0029] Preferably, in step B, the solvent for dissolving Ni-MOF includes at least one of methanol, ethanol, ethylene glycol, methyl butyl ketone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile and 1,4-dioxane.
[0030] Furthermore, the temperature of the second reaction is 273-303 K, and the time is 5-30 min.
[0031] Preferably, the temperature of the third reaction is 300-500K, and the time is 8-24h.
[0032] Preferably, in step C, the mass ratio of nickel salt to organic ligand is 1:0.5-2.
[0033] Preferably, the added amount of the Ni-MOF / Fe is 20-80% of the mass of the nickel salt.
[0034] The second aspect of the present invention provides a Ni-MOF / Fe / Ni-MOF, which is prepared by the preparation method described in the first aspect.
[0035] The third aspect of the present invention provides a magnesium-based composite hydrogen storage material including MgH2 and the Ni-MOF / Fe / Ni-MOF.
[0036] Furthermore, the proportion of Ni-MOF / Fe / Ni-MOF is 2-20%.
[0037] The fourth aspect of the present invention provides a method for preparing the magnesium-based composite hydrogen storage material, which can be obtained by mixing MgH2 and Ni-MOF / Fe / Ni-MOF through ball milling.
[0038] Compared with the prior art, the present invention has at least the following beneficial effects:
[0039] The preparation method of Ni-MOF / Fe / Ni-MOF provided by the present invention forms a metal frame into a sandwich layered structure through a three-step method, thereby ensuring that nickel and iron maintain a nano-grain size and are embedded in the layered structure.
[0040] The Ni-MOF / Fe / Ni-MOF provided by the present invention has both core-shell functions. The porous structure of Ni-MOF is used as a nanoreactor, which not only accelerates the catalytic reaction rate, but also improves the stability of the composite catalyst due to the restraining effect of Ni-MOF. The layered structure has a large specific surface area and numerous unsaturated active sites, which can greatly improve its catalytic performance.
[0041] The magnesium-based composite hydrogen storage material provided by the present invention uses Ni-MOF / Fe / Ni-MOF as a catalyst. Ni-MOF / Fe / Ni-MOF generates mutual conversion between Mg2NiH4 / Mg2Ni and FeH6Mg2 / Fe during the process of hydrogen absorption and desorption, and synergistic catalysis improves the hydrogen storage performance of MgH2. During the hydrogen desorption process, Mg2NiH4 is generated to act as a "hydrogen pump" to quickly transport hydrogen and promote hydrogen diffusion. At the same time, α-Fe accelerates the nucleation and growth of Mg by reducing the nucleation energy of Mg from MgH2.
[0042] The preparation method of the magnesium-based composite hydrogen storage material provided by the present invention combines Ni-MOF / Fe / Ni-MOF with MgH2 through a solid-phase reaction of ball milling mixing. The implementation of this method not only simplifies the preparation process, but also significantly improves the batch processing volume, making the production process more efficient, and is very suitable for industrial large-scale production, providing strong support for the commercialization and large-scale application of hydrogen energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 A scanning electron microscope image of Ni-MOF / Fe / Ni-MOF provided in Example 1;
[0045] Figure 2 XRD spectra provided for characterization example 2;
[0046] Figure 3 This is the hydrogen release curve obtained in Test Example 3. DETAILED DESCRIPTION
[0047] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but those skilled in the art will understand that the following embodiments and examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0048] The first aspect of the present invention provides a method for preparing Ni-MOF / Fe / Ni-MOF, comprising the following steps:
[0049] A. Mix the nickel salt solution and the organic ligand solution evenly for a first reaction, and then separate, dry and activate to obtain Ni-MOF;
[0050] B. After dissolving the Ni-MOF, adding iron salt and a reducing agent to carry out a second reaction to obtain Ni-MOF / Fe;
[0051] C. After the nickel salt solution and the organic ligand solution are uniformly mixed, the Ni-MOF / Fe is added to carry out a third reaction to obtain the Ni-MOF / Fe / Ni-MOF.
[0052] The preparation method of Ni-MOF / Fe / Ni-MOF provided by the present invention forms a metal frame into a sandwich layered structure through a three-step method, thereby ensuring that nickel and iron maintain a nano-grain size and are embedded in the layered structure.
[0053] Furthermore, the concentration of the nickel salt solution is 1 to 20 mg / mL.
[0054] Typically but not limiting, the concentration of the nickel salt solution can be, for example, 1 mg / mL, mg / mL, 2 mg / mL, 3 mg / mL, 5 mg / mL, 10 mg / mL, 12 mg / mL, 15 mg / mL or 20 mg / mL, or any value within the range of 1 to 20 mg / mL.
[0055] Preferably, the concentration of the organic ligand solution is 1-20 mg / mL.
[0056] Typically but not limiting, the concentration of the organic ligand solution can be, for example, 1 mg / mL, mg / mL, 2 mg / mL, 3 mg / mL, 5 mg / mL, 10 mg / mL, 12 mg / mL, 15 mg / mL or 20 mg / mL, or any value within the range of 1 to 20 mg / mL.
[0057] Preferably, in step A, the mass ratio of nickel salt to organic ligand is 1:0.1-2. Within this range, the nickel salt can fully react with the organic ligand to form Ni-MOF.
[0058] Typically but not limiting, the mass ratio of nickel salt to organic ligand can be, for example, 1:0.1, 1:0.2, 1:0.3, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5 or 1:2, or any value within the range of 1:0.1 to 2.
[0059] It should be noted that the nickel salt here refers to the nickel salt in the nickel salt solution, and the organic ligand refers to the organic ligand in the organic ligand solution.
[0060] Furthermore, the nickel salt in the nickel salt solution includes at least one of nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel phosphate, nickel carbonate and nickel oxalate.
[0061] Preferably, the solvent in the nickel salt solution includes at least one of methanol, ethanol, ethylene glycol, methyl butyl ketone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile and 1,4-dioxane.
[0062] Preferably, the organic ligand comprises a benzoic acid compound.
[0063] Preferably, the benzoic acid compound includes at least one of terephthalic acid, isophthalic acid, phthalic acid, trimesic acid, pyromellitic acid and mellitic acid.
[0064] Preferably, the solvent in the organic ligand solution includes at least one of methanol, ethanol, ethylene glycol, methyl butyl ketone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile and 1,4-dioxane.
[0065] Furthermore, the temperature of the first reaction is 300-600K, and the time is 1-10 hours. During the first reaction, the divalent nickel ions in the nickel salt and the carboxylic acid groups in the benzoic acid compound undergo a coordination reaction.
[0066] Typically but not limiting, the temperature of the first reaction may be, for example, 303 K, 323 K, K, 343 K, 373 K, 403 K, 423 K, 453 K, 503 K, 533 K or 573 K, or any value in the range of 300 to 600 K. The time of the first reaction may be, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 8 h, 10 h, or any value in the range of 1 to 10 h.
[0067] Preferably, the drying activation temperature is 300-500K, and the time is 8-24h. During the drying activation process, the Ni-MOF will gradually open up its pore structure as the solvent molecules are removed, exposing more active sites.
[0068] Typically but not limiting, the drying activation temperature may be, for example, 333 K, 343 K, 353 K, 363 K, 373 K, 393 K, 423 K, 453 K, 483 K or 493 K, or any value within the range of 300 to 500 K. The drying activation time may be, for example, 8 h, 9 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h or 24 h, or any value within the range of 8 to 24 h.
[0069] Furthermore, the iron salt includes at least one of ferric nitrate, ferric chloride, ferric sulfate, ferric acetate, ferric phosphate, ferric carbonate and ferric oxalate.
[0070] Preferably, the amount of the iron salt added is 20-80% of the mass of Ni-MOF. Within this range, iron as the core layer of Ni-MOF / Fe / Ni-MOF has the effect of coordinating the charging and releasing of hydrogen with the Ni-MOF catalytic material.
[0071] Typically but not limiting, the amount of iron salt added is 20%, 25%, 30%, 40%, 50%, 60% or 80% of the mass of Ni-MOF, and can be any value within the range of 20-80%.
[0072] Preferably, the reducing agent comprises at least one of sodium borohydride, lithium aluminum hydride, lithium borohydride, sodium cyanoborohydride, lithium triethylborohydride, dimethyl borane and THF borane.
[0073] Preferably, the amount of the reducing agent added is 10 to 90% of the mass of Ni-MOF.
[0074] Typically but not limiting, the amount of reducing agent added is 10%, 20%, 30%, 40%, 50%, 70% or 90% of the mass of Ni-MOF, and can be any value within the range of 10-90%.
[0075] Preferably, in step B, the solvent for dissolving Ni-MOF includes at least one of methanol, ethanol, ethylene glycol, methyl butyl ketone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile and 1,4-dioxane.
[0076] Furthermore, the temperature of the second reaction is 273-303 K, the time is 5-30 min, and during the second reaction, the reducing agent reduces the divalent iron to elemental iron.
[0077] Typically but not limiting, the temperature of the second reaction may be, for example, 273 K, 274 K, K, 275 K, 278 K, 283 K, 285 K, 293 K, 295 K, 300 K or 303 K, or any value within the range of 273 to 303 K. The time of the second reaction may be, for example, 5 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 25 min or 30 min, or any value within the range of 5 to 30 min.
[0078] Preferably, the temperature of the third reaction is 300-500K, and the time is 8-24h. During the third reaction, the divalent nickel ions in the nickel salt still undergo coordination reaction with the carboxylic acid groups in the benzoic acid compound to generate another layer of Ni-MOF.
[0079] Typically but not limiting, the temperature of the third reaction may be, for example, 303 K, 313 K, 323 K, 333 K, 353 K, 373 K, 393 K, 413 K, 433 K, 453 K or 483 K, or any value in the range of 300 to 500 K. The time of the third reaction may be, for example, 8 h, 9 h, 10 h, 12 h, 15 h, 18 h, 20 h, 22 h or 24 h, or any value in the range of 8 to 24 h.
[0080] Preferably, in step C, the mass ratio of nickel salt to organic ligand is 1:0.5-2.
[0081] Preferably, the added amount of the Ni-MOF / Fe is 20-80% of the mass of the nickel salt.
[0082] Typically but not limiting, the amount of Ni-MOF / Fe added is 20%, 25%, 30%, 40%, 50%, 60% or 80% of the mass of the nickel salt, and can be any value within the range of 20-80%.
[0083] The second aspect of the present invention provides a Ni-MOF / Fe / Ni-MOF, which is prepared by the preparation method described in the first aspect.
[0084] The Ni-MOF / Fe / Ni-MOF provided by the present invention has both core-shell functions. The porous structure of Ni-MOF is used as a nanoreactor, which not only accelerates the catalytic reaction rate, but also improves the stability of the composite catalyst due to the restraining effect of Ni-MOF. The layered structure has a large specific surface area and numerous unsaturated active sites, which can greatly improve its catalytic performance.
[0085] The third aspect of the present invention provides a magnesium-based composite hydrogen storage material including MgH2 and the Ni-MOF / Fe / Ni-MOF.
[0086] The magnesium-based composite hydrogen storage material provided by the present invention uses Ni-MOF / Fe / Ni-MOF as a catalyst. Ni-MOF / Fe / Ni-MOF generates mutual conversion between Mg2NiH4 / Mg2Ni and FeH6Mg2 / Fe during the process of hydrogen absorption and desorption, and synergistic catalysis improves the hydrogen storage performance of MgH2. During the hydrogen desorption process, Mg2NiH4 is generated to act as a "hydrogen pump" to quickly transport hydrogen and promote hydrogen diffusion. At the same time, α-Fe accelerates the nucleation and growth of Mg by reducing the nucleation energy of Mg from MgH2.
[0087] Furthermore, the proportion of Ni-MOF / Fe / Ni-MOF is 2-20%. Within this proportion range, the magnesium-based composite hydrogen storage material can achieve an ideal hydrogen charging and discharging amount and greatly improve the hydrogen storage rate.
[0088] Typically but not limiting, the ratio of Ni-MOF / Fe / Ni-MOF can be, for example, 2%, 5%, 10%, 12%, 15%, 18% or 20%, or any value within the range of 2 to 20%.
[0089] It should be noted that the ratio of Ni-MOF / Fe / Ni-MOF refers to its mass ratio in the magnesium-based composite hydrogen storage material.
[0090] The fourth aspect of the present invention provides a method for preparing the magnesium-based composite hydrogen storage material, which can be obtained by mixing MgH2 and Ni-MOF / Fe / Ni-MOF through ball milling.
[0091] The preparation method of the magnesium-based composite hydrogen storage material provided by the present invention combines Ni-MOF / Fe / Ni-MOF with MgH2 through a solid-phase reaction of ball milling mixing. The implementation of this method not only simplifies the preparation process, but also significantly improves the batch processing volume, making the production process more efficient, and is very suitable for industrial large-scale production, providing strong support for the commercialization and large-scale application of hydrogen energy.
[0092] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0093] Example 1
[0094] This embodiment provides a Ni-MOF / Fe / Ni-MOF, and the preparation method is as follows:
[0095] 1. Preparation of Ni-MOF
[0096] Take 25mL of nickel nitrate hexahydrate in ethylene glycol (4.0mg / mL) and 10mL of trimesic acid in DMF (7.5mg / mL), stir at room temperature for 5 minutes, and stir at 393K for another 2 hours. The resulting precipitate is extracted by centrifugation, washed several times with DMF and anhydrous ethanol. Finally, it is dried and activated under vacuum conditions at 373K for 12h.
[0097] 2. Preparation of Ni-MOF / Fe
[0098] Weigh 60.0 mg of Ni-MOF and dissolve it in 20 mL of DMF and stir evenly. Then add 48.0 mg of FeCl2·4H2O and keep stirring at a low temperature of 5°C. Then add 42.0 mg of NaBH4 and react for 5 to 10 minutes. The product is washed several times with DMF and anhydrous ethanol and dried at 333K in vacuum for 12 hours to finally obtain Ni-MOF / Fe particles.
[0099] 3. Preparation of Ni-MOF / Fe / Ni-MOF
[0100] 8.0 mL of nickel nitrate hexahydrate in ethylene glycol (6.0 mg / mL) was mixed with 8.0 mL of trimesic acid in DMF (5.0 mg / mL), and then 24.0 mg of Ni-MOF / Fe particles were added to form a Ni-MOF shell. The mixture was stirred at 363 K for 12 h, and the dark gray precipitate was collected by centrifugation, washed with DMF and ethanol, and dried at 333 K in vacuum for 8 h.
[0101] Example 2
[0102] This embodiment provides a Ni-MOF / Fe / Ni-MOF, and the preparation method is as follows:
[0103] 1. Preparation of Ni-MOF
[0104] Take 25mL of nickel nitrate hexahydrate in ethylene glycol (concentration of 3.0mg / mL) and mix with 10mL of trimesic acid in DMF (concentration of 5mg / mL), stir at room temperature for 5 minutes, and stir at 393K for another 2 hours. The resulting precipitate is extracted by centrifugation, washed several times with DMF and anhydrous ethanol. Finally, it is dried and activated under vacuum conditions at 373K for 12h.
[0105] 2. Preparation of Ni-MOF / Fe
[0106] Weigh 50 mg of Ni-MOF and dissolve it in 20 mL of DMF and stir evenly. Then add 30 mg of FeCl2·4H2O and keep stirring at 5°C. Then add 25 mg of NaBH4 and react for 5 to 10 minutes. The product is washed several times with DMF and anhydrous ethanol and dried at 333K in vacuum for 12 hours to finally obtain Ni-MOF / Fe particles.
[0107] 3. Preparation of Ni-MOF / Fe / Ni-MOF
[0108] 10 mL of nickel nitrate hexahydrate in ethylene glycol (5.0 mg / mL) was mixed with 10 mL of trimesic acid in DMF (4.0 mg / mL), and then 24.0 mg of Ni-MOF / Fe particles were added to form a Ni-MOF shell. The mixture was stirred at 363 K for 12 h, and the dark gray precipitate was collected by centrifugation, washed with DMF and ethanol, and dried at 333 K in vacuum for 8 h.
[0109] Example 3
[0110] This embodiment provides a Ni-MOF / Fe / Ni-MOF, and the preparation method is as follows:
[0111] 1. Preparation of Ni-MOF
[0112] Take 25mL of nickel nitrate hexahydrate in ethylene glycol (concentration of 5.0mg / mL) and mix with 10mL of trimesic acid in DMF (concentration of 10mg / mL), stir at room temperature for 5 minutes, and stir at 393K for another 2 hours. The resulting precipitate is extracted by centrifugation, washed several times with DMF and anhydrous ethanol. Finally, it is dried and activated under vacuum conditions at 373K for 12h.
[0113] 2. Preparation of Ni-MOF / Fe
[0114] Weigh 80 mg of Ni-MOF and dissolve it in 20 mL of DMF and stir evenly. Then add 60 mg of FeCl2·4H2O and keep stirring at 5°C. Then add 50 mg of NaBH4 and react for 5 to 10 minutes. The product is washed several times with DMF and anhydrous ethanol and dried at 333K in vacuum for 12 hours to finally obtain Ni-MOF / Fe particles.
[0115] 3. Preparation of Ni-MOF / Fe / Ni-MOF
[0116] 15 mL of nickel nitrate hexahydrate in ethylene glycol (8 mg / mL) was mixed with 15 mL of trimesic acid in DMF (7.5 mg / mL), and then 24.0 mg of Ni-MOF / Fe particles were added to form a Ni-MOF shell. The mixture was stirred at 363 K for 12 h, and the dark gray precipitate was collected by centrifugation, washed with DMF and ethanol, and dried at 333 K in vacuum for 8 h.
[0117] Example 4
[0118] This embodiment provides a Ni-MOF / Fe / Ni-MOF, and the preparation method is as follows:
[0119] 1. Preparation of Ni-MOF
[0120] 25 mL of nickel nitrate hexahydrate in ethylene glycol (8.0 mg / mL) was mixed with 10 mL of trimesic acid in DMF (15 mg / mL), stirred at room temperature for 5 minutes, and stirred at 393 K for another 2 hours. The resulting precipitate was extracted by centrifugation, washed several times with DMF and anhydrous ethanol, and finally dried and activated under vacuum at 373 K for 12 hours.
[0121] 2. Preparation of Ni-MOF / Fe
[0122] Weigh 100 mg of Ni-MOF and dissolve it in 20 mL of DMF and stir evenly. Then add 75 mg of FeCl2·4H2O and keep stirring at 5°C. Then add 50 mg of NaBH4 and react for 5 to 10 minutes. The product is washed several times with DMF and anhydrous ethanol and dried at 333K in vacuum for 12 hours to finally obtain Ni-MOF / Fe particles.
[0123] 3. Preparation of Ni-MOF / Fe / Ni-MOF
[0124] 20 mL of ethylene glycol solution of nickel nitrate hexahydrate (concentration of 10 mg / mL) was mixed with 20 mL of DMF solution of trimesic acid (concentration of 15 mg / mL), and then 24.0 mg of Ni-MOF / Fe particles were added to form a Ni-MOF shell. The mixture was stirred at 363K for 12 h, and the dark gray precipitate was collected by centrifugation, washed with DMF and ethanol, and dried at 333K under vacuum for 8 h.
[0125] Example 5
[0126] This embodiment provides a Ni-MOF / Fe / Ni-MOF, which is different from Example 1 in that in step 2, the amount of FeCl2·4H2O added is 12 mg, the amount of NaBH4 added is 10 mg, and the remaining steps are the same as those in Example 1, which will not be repeated here.
[0127] Example 6
[0128] This embodiment provides a Ni-MOF / Fe / Ni-MOF, which is different from Example 1 in that in step 2, the amount of FeCl2·4H2O added is 48 mg, the amount of NaBH4 added is 40 mg, and the remaining steps are the same as those in Example 1, which will not be repeated here.
[0129] Example 7
[0130] This embodiment provides a Ni-MOF / Fe / Ni-MOF, which is different from Embodiment 1 in that the amount of Ni-MOF / Fe added in step 3 is 10 mg, and the remaining steps are the same as those in Embodiment 1, which will not be repeated here.
[0131] Example 8
[0132] This embodiment provides a Ni-MOF / Fe / Ni-MOF, which is different from Example 1 in that the amount of Ni-MOF / Fe added in step 3 is 50 mg, and the remaining steps are the same as those in Example 1, which will not be repeated here.
[0133] Example 9
[0134] This embodiment provides a Ni-MOF / Fe / Ni-MOF, which is different from Example 1 in that, in step 1, 25 mL of ethylene glycol solution of nickel nitrate hexahydrate (concentration of 5.0 mg / mL) is mixed with 10 mL of DMF solution of trimesic acid (concentration of 1.0 mg / mL), and the remaining steps are the same as those in Example 1 and are not repeated here.
[0135] Example 10
[0136] This embodiment provides a Ni-MOF / Fe / Ni-MOF, which is different from Example 1 in that, in step 1, 25 mL of ethylene glycol solution of nickel nitrate hexahydrate (concentration of 4.0 mg / mL) is mixed with 10 mL of DMF solution of trimesic acid (concentration of 20.0 mg / mL), and the remaining steps are the same as those in Example 1 and are not repeated here.
[0137] Comparative Example 1
[0138] This comparative example provides a Ni-MOF, which is different from Example 1 in that Step 2 and Step 3 are omitted.
[0139] Comparative Example 2
[0140] This comparative example provides a Ni-MOF / Fe, which differs from Example 1 in that step 3 is omitted.
[0141] Examples 11-20
[0142] These embodiments provide a magnesium-based composite hydrogen storage material, in which MgH2 and Ni-MOF / Fe / Ni-MOF prepared in embodiments 1-10 are compounded by ball milling in a mass ratio of 9:1 to obtain a magnesium-based composite hydrogen storage material.
[0143] Embodiment 21
[0144] This embodiment provides a magnesium-based composite hydrogen storage material, and MgH2 and Ni-MOF / Fe / Ni-MOF prepared in Example 1 are compounded by ball milling at a mass ratio of 49:1 to obtain a magnesium-based composite hydrogen storage material.
[0145] Embodiment 22
[0146] This embodiment provides a magnesium-based composite hydrogen storage material, and MgH2 and Ni-MOF / Fe / Ni-MOF prepared in Example 1 are compounded by ball milling at a mass ratio of 4:1 to obtain a magnesium-based composite hydrogen storage material.
[0147] Comparative Examples 3-4
[0148] These comparative examples provide a magnesium-based composite hydrogen storage material, in which MgH2 and Ni-MOF and Ni-MOF / Fe prepared in comparative examples 1-2 are compounded by ball milling in a mass ratio of 9:1 to obtain a magnesium-based composite hydrogen storage material.
[0149] Comparative Example 5
[0150] This comparative example provides a magnesium-based hydrogen storage material, MgH2.
[0151] Characterization Example 1
[0152] The Ni-MOF / Fe / Ni-MOF obtained in Example 1 was subjected to a scanning electron microscope, and the obtained image is as follows Figure 1 shown.
[0153] from Figure 1 As can be seen in Figure (a), the grains of the MOF structure of Ni-MOF / Fe / Ni-MOF are relatively uniform and are connected together by clusters of microspheres with diameters of 100 to 200 nm; Figure 1 Figure (b) shows the overall structure of Ni-MOF / Fe / Ni-MOF. Rod-shaped elemental iron structures are interspersed between the spheres. They have a rough surface area and can provide more nucleation sites and larger hydrogen diffusion channels.
[0154] Characterization Example 2
[0155] The magnesium-based composite hydrogen storage material obtained in Example 11 was charged with hydrogen, and XRD was performed after reaching a saturated state; then hydrogen was released, and XRD was continued after the hydrogen was completely released. The obtained spectrum corresponds to the following: Figure 2 shown.
[0156] from Figure 2 It can be seen that after hydrogenation, the magnesium-based composite material has three phases: Mg2NiH4, FeH6Mg2 and Fe; and after hydrogenation, they are converted into Mg2Ni and Fe respectively, which synergistically catalyze and improve the hydrogen storage performance of MgH2.
[0157] Test Example 1
[0158] DSC Testing
[0159] Test samples: hydrogen storage materials of Examples and Comparative Examples.
[0160] Test method: A thermogravimetric analyzer is used to test the sample that has reached saturation with hydrogen absorption at different heating rates to obtain the peak hydrogen desorption temperature at different heating rates.
[0161] The test results are shown in Table 1 below:
[0162] Table 1
[0163]
[0164] As shown in Table 1, the DSC test results of the magnesium-based composite material of Example 11 show that at different heating rates, the peak temperature at a heating rate of 5°C / min drops to below 329.9°C, the peak temperature at a heating rate of 10°C / min drops to below 357.2°C, the peak temperature at a heating rate of 15°C / min drops to below 368.7°C, and the peak temperature at a heating rate of 20°C / min drops to below 382.1°C. This indicates that the peak temperature of hydrogen desorption of the magnesium-based composite material provided by the present invention is significantly reduced, and the thermodynamic properties are significantly improved.
[0165] Test Example 2
[0166] Hydrogen absorption and desorption kinetic cycle stability test
[0167] Test samples: hydrogen storage materials provided in Examples and Comparative Examples.
[0168] Test method: The sample was subjected to a hydrogen absorption and desorption cycle stability test at a fixed temperature of 350°C and a fixed hydrogen pressure of 3.0 MPa. The hydrogen absorption and desorption time were both 15 minutes.
[0169] The test results are shown in Table 2 below:
[0170] Table 2
[0171]
[0172] As shown in Table 2, the magnesium-based composite material of Example 11 and its preparation method have stable hydrogen storage cycle dynamic performance. In the initial 15 minutes, the alloy absorbed 6.502wt.%H2, and after 10 cycles, the hydrogen absorption capacity was 6.328wt.%H2, and the retention rate of the hydrogen absorption capacity was above 97.3%. In the initial 15 minutes, the alloy released 6.079wt.%H2, and after 10 cycles, the hydrogen release capacity was 5.895wt.%H2, and the retention rate of the hydrogen release capacity was still above 97.0%.
[0173] Test Example 3
[0174] The hydrogen storage materials of Example 11 and Comparative Example 5 that were saturated with hydrogen were subjected to a hydrogen release experiment.
[0175] The specific steps are as follows: the hydrogen-saturated sample of Example 11 releases hydrogen at 250° C. and 0 MPa for 120 min; the hydrogen-saturated sample of Comparative Example 5 releases hydrogen at 300° C. and 0 MPa for 120 min.
[0176] The hydrogen release curve corresponds to Figure 3 shown.
[0177] from Figure 3 It can be seen that within the same 120 min, the hydrogen desorption rate and amount of the magnesium-based composite material of Example 11 at 250°C are much greater than the hydrogen desorption rate and amount of the pure MgH2 of Comparative Example 5 at 300°C.
[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing Ni-MOF / Fe / Ni-MOF, characterized in that: The following steps are involved: A. Mix the nickel salt solution and the organic ligand solution evenly for a first reaction, and then separate, dry and activate to obtain Ni-MOF; B. After dissolving the Ni-MOF, adding iron salt and a reducing agent to carry out a second reaction to obtain Ni-MOF / Fe; C. After the nickel salt solution and the organic ligand solution are uniformly mixed, the Ni-MOF / Fe is added to carry out a third reaction to obtain the Ni-MOF / Fe / Ni-MOF.
2. The preparation method according to claim 1, characterized in that: The concentration of the nickel salt solution is 1 to 20 mg / mL; Preferably, the concentration of the organic ligand solution is 1 to 20 mg / mL; Preferably, in step A, the mass ratio of nickel salt to organic ligand is 1:0.1-2.
3. The preparation method according to claim 1, characterized in that: The nickel salt in the nickel salt solution includes at least one of nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel phosphate, nickel carbonate and nickel oxalate; Preferably, the solvent in the nickel salt solution includes at least one of methanol, ethanol, ethylene glycol, methyl butyl ketone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile and 1,4-dioxane; Preferably, the organic ligand comprises a benzoic acid compound; Preferably, the benzoic acid compound includes at least one of terephthalic acid, isophthalic acid, phthalic acid, trimesic acid, pyromellitic acid and mellitic acid; Preferably, the solvent in the organic ligand solution includes at least one of methanol, ethanol, ethylene glycol, methyl butyl ketone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile and 1,4-dioxane.
4. The preparation method according to claim 1, characterized in that: The temperature of the first reaction is 300-600K, and the time is 1-10h; Preferably, the drying activation temperature is 300-500K and the time is 8-24h.
5. The preparation method according to claim 1, characterized in that: The iron salt includes at least one of ferric nitrate, ferric chloride, ferric sulfate, ferric acetate, ferric phosphate, ferric carbonate and ferric oxalate; Preferably, the amount of the iron salt added is 20 to 80% of the mass of Ni-MOF; Preferably, the reducing agent comprises at least one of sodium borohydride, lithium aluminum hydride, lithium borohydride, sodium cyanoborohydride, lithium triethylborohydride, dimethyl sulfide borane and THF borane; Preferably, the amount of the reducing agent added is 10 to 90% of the mass of Ni-MOF; Preferably, in step B, the solvent for dissolving Ni-MOF includes at least one of methanol, ethanol, ethylene glycol, methyl butyl ketone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile and 1,4-dioxane.
6. The preparation method according to claim 1, characterized in that: The temperature of the second reaction is 273-303K and the time is 5-30min; Preferably, the temperature of the third reaction is 300-500K, and the time is 8-24h; Preferably, in step C, the mass ratio of nickel salt to organic ligand is 1:0.5-2; Preferably, the added amount of the Ni-MOF / Fe is 20-80% of the mass of the nickel salt.
7. A Ni-MOF / Fe / Ni-MOF, characterized in that The preparation method is described in any one of claims 1 to 6.
8. A magnesium-based composite hydrogen storage material, characterized in that: Comprises MgH2 and the Ni-MOF / Fe / Ni-MOF described in claim 7.
9. The magnesium-based composite hydrogen storage material according to claim 8, characterized in that: The proportion of Ni-MOF / Fe / Ni-MOF is 2-20%.
10. A method for preparing the magnesium-based composite hydrogen storage material according to claim 8 or 9, characterized in that: MgH2 and Ni-MOF / Fe / Ni-MOF are mixed by ball milling to obtain the magnesium-based composite hydrogen storage material.
Citation Information
Cited By
MOF structure modification-based high-capacity magnesium-based composite material and preparation method thereof
CN121180944A